2023
DOI: 10.1101/2023.02.27.530143
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Latitude-specific urbanization effects on life history traits in the damselflyIschnura elegans

Abstract: Many species are currently adapting to cities at different latitudes. Adaptation to urbanization may require eco-evolutionary changes in response to temperature and invasive species that may differ between latitudes.Here, we studied single and combined effects of increased temperatures and invasive alien predator presence on the phenotypic response of replicated urban and rural populations of the damselflyIschnura elegansand contrasted these between central and high latitudes.Larvae were exposed to temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 50 publications
(77 reference statements)
0
6
0
Order By: Relevance
“…However, these differences could also stem from geographically varying interaction between urbanization and other environmental factors the damselflies face. Indeed, the results of a common‐garden experiment carried out by Palomar et al (2023) indicated that urban I. elegans , and especially males, were lighter and had a lower growth rate than rural individuals and that these phenotypic changes partially depended on the sampling latitude and rearing temperature. Such phenotypic variation was associated with adjustment of damselfly life history to warmer urban conditions likely imposing weaker seasonal time constraints and hence reduced larval growth rate compared to rural damselflies (Palomar et al, 2023; Tüzün, Op de Beeck, & Stoks, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, these differences could also stem from geographically varying interaction between urbanization and other environmental factors the damselflies face. Indeed, the results of a common‐garden experiment carried out by Palomar et al (2023) indicated that urban I. elegans , and especially males, were lighter and had a lower growth rate than rural individuals and that these phenotypic changes partially depended on the sampling latitude and rearing temperature. Such phenotypic variation was associated with adjustment of damselfly life history to warmer urban conditions likely imposing weaker seasonal time constraints and hence reduced larval growth rate compared to rural damselflies (Palomar et al, 2023; Tüzün, Op de Beeck, & Stoks, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…For example, a recent study on larvae of I. elegans and its prey Daphnia magna provided evidence for cryptic eco‐evolutionary feedback masking the effects of adaptation to urbanization, at the same time confirming an adaptive response of I. elegans to urbanization (Brans et al, 2022). Furthermore, there is evidence that the phenotypic adaptation to urbanization might be temperature and latitude‐dependent (Palomar et al, 2023), increasing the levels of complexity in the study of urban adaptation in ectotherms. Studies of other highly mobile animals, including insects such as bumblebees (Theodorou et al, 2018) indicate that the genomic signal of adaptation to urbanization is often detectable despite the risk of dampening local adaptation through maladaptive gene flow (Lenormand, 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…How the impact posed by biological invasions to ecosystems change with warming is an important global issue, but it is very difficult to predict whether the impact will be severe or mild owing to the complexity of its process and mechanisms (e.g. [57]). On the other hand, our finding that 'threats by poleward-expanding species that invade from warmer regions become severe with warming' would be applied to other cases of biological invasions attributed to global warming.…”
Section: Discussionmentioning
confidence: 99%
“…The dataset containing the phenotypic data is included in Table S3 and is available on Figshare https://doi.org/10.6084/m9.figshare.23708748.v2 (Palomar et al, 2023 ).…”
Section: Data Availability Statementmentioning
confidence: 99%